Dextran sulfate blocks antibody binding to the principal neutralizing domain of human immunodeficiency virus type 1 without interfering with gp120-CD4 interactions. - Callahan, L N (1991)
The mechanism of the antiviral activity of sulfated polysaccharides on human immunodeficiency virus type 1 (HIV-1) was investigated by determining the effect of dextran sulfate on the binding of CD4 and several anti-gp120 monoclonal antibodies to both recombinant and cell surface gp120. Dextran sulfate did not interfere with the binding of sCD4 to rgp120 on enzyme-linked immunosorbent assay (ELISA) plates or in solution and did not block sCD4 binding to HIV-1-infected cells expressing gp120 on the cell surface. Dextran sulfate had minimal effects on rgp120 binding to CD4+ cells at concentrations which effectively prevent HIV replication. In contrast, it potently inhibited the binding of both rgp120 and cell surface gp120 to several monoclonal antibodies directed against the principal neutralizing domain of gp120 (V3). In an ELISA format, dextran sulfate enhanced the binding of monoclonal antibodies against amino-terminal regions of gp120 and had no effect on antibodies directed to other regions of gp120, including the carboxy terminus. The inhibitory effects of polyanionic polysaccharides on viral binding, viral replication, and formation of syncytia therefore appear mediated by interactions with positively charged amino acids concentrated in the V3 region. This high local positive charge density, unique to the V3 loop, leads us to propose that this property is critical to the function of the V3 region in mediating envelope binding and subsequent fusion between viral and cell membranes. The specific interaction of dextran sulfate with this domain suggests that structurally related molecules on the cell surface, such as heparan sulfate, may be additional targets for HIV binding and infection.